C-reactive protein in urologic cancers. (November 2015) - Huang, Jonathan; Baum, Yoram; Alemozaffar, Mehrdad; Ogan, Kenneth; Harris, Wayne; Kucuk, Omer; Master, Viraj A.
Abstract: C-reactive protein is an acute-phase reactant that is elevated in the setting of systemic infections, trauma, and malignancies. Urologic cancers have been shown to promote changes in c-reactive protein levels. Pre-treatment serum levels can predict disease characteristics, extent of disease, and prognosticate survival after intervention in renal cell carcinoma, prostate cancer, bladder cancer, upper tract urothelial carcinoma, and penile cancer. Changes in post-treatment serum levels have also shown promise in determining survival. As a result, c-reactive protein has been incorporated into various survival nomograms to improve predictive accuracy. While the association between c-reactive protein and survival in testicular cancer has not been studied, elevated serum levels may correlate with treatment side effects, such as cardiovascular disease and chronic cancer-related fatigue. Understanding the relationship between c-reactive protein and urologic cancers can help physicians determine the appropriate course of treatment and improve patient care.